Reasonable accommodation as the main instrument in countering discrimination based on disability in employment - Drożdż, Justyna (Undesirable Phenomena in Employment from the Perspective of Labour Law - Selected Issues, 2023)
The concept of reasonable accommodation for persons with disabilities and the employer’s obligation to implement it has been extensively described in the doctrine, given its ambiguous recognition in international or national legislation. By analysing national and European jurisprudence, literature, reports and so-called good practices, this chapter will be dedicated to any necessary changes adapter to the needs of people with disabilities in the workplace, so-called reasonable accommodation, to combat discrimination inemployment.